2019
DOI: 10.3390/ma12010122
|View full text |Cite
|
Sign up to set email alerts
|

Research on High Performance Milling of Engineering Ceramics from the Perspective of Cutting Variables Setting

Abstract: The setting of cutting variables for precision milling of ceramics is important to both the machined surface quality and material removal rate (MRR). This work specifically aims at the performance of corner radius PCD (polycrystalline diamond) end mill in precision milling of zirconia ceramics with relatively big cutting parameters. The characteristics of the cutting zone in precision milling ceramics with corner radius end mill are analyzed. The relationships between the maximum uncut chip thickness (hmax) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In the case of typical difficult-to-cut materials, keeping high machined surface quality and improving machining efficiency has always been a key issue [ 28 ]. Considerable efforts have been made to improve the cutting performance of carbide tools in conditions without cooling and lubricating fluids and at elevated cutting speeds, when the carbide tool is subjected to more severe friction and wear, leading to the reduction of service life [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of typical difficult-to-cut materials, keeping high machined surface quality and improving machining efficiency has always been a key issue [ 28 ]. Considerable efforts have been made to improve the cutting performance of carbide tools in conditions without cooling and lubricating fluids and at elevated cutting speeds, when the carbide tool is subjected to more severe friction and wear, leading to the reduction of service life [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…River gravel can also be used in concrete and is used in concrete but of non-standard strength as there is still no standard for river gravel for its use in concrete in civil engineering work. As river gravel is very cheap to source so, if the goal is to reduce the cost of construction it can be used in places like walkways or places where no heavy loads of structure are applied [21].…”
Section: E River Gravelmentioning
confidence: 99%
“…Various studies have shown that defects formed at various stages of manufacturing ceramic parts and tools (hot sintering of workpieces and diamond sharpening) increase the probability of brittle fracture and hinder the industrial use of ceramics [4][5][6]. In addition, the presence of a defective layer can limit the functional characteristics of various coatings, the deposition of which is often used as a finishing operation in the technological process of ceramic products' manufacturing for the needs of mechanical engineering [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%